Determinants of Hospital Nurse Burnout: The Moderating Role of Supervision - Budi Santoso; Ferdic Sukma; Indra Fahrizal; Syaiful Munir; Bagus Shandy Narmaditya (Asian Journal for Public Opinion Research)
Health care has become a rapidly growing industry where the role of nurses as a group of emotional labor employees is central and prone to burnout. The purpose of this study was to examine the role of supervision in moderating burnout caused by the effect of work intensity, customer contact, and self-efficacy, where the moderating role of supervision on burnout with its various predictors is still unstable. This quantitative study was based on research samples collected through questionnaires from 131 hospital nurses spread over two different locations. The questionnaire asked about supervision, work intensity, customer contact, self-efficacy and burnout used a Likert scale, which was then analyzed using SEM-PLS. The results indicated that work intensity and self-efficacy had a significant effect on burnout, while customer contact had no significant effect on burnout. Supervision as a moderator only significantly moderates the effect of work intensity on burnout, while supervision is not significant as a moderating variable on the effect of customer contact and self-efficacy on burnout. This study can contribute to the development of theories about burnout and practically can be used as a reference by policy makers in enhancing the role of supervision for nurses in hospitals.